The relationship of industrial digitalization with dynamic changes in the labor economy of the region in the context of Industry 4.0 and 5.0 - Kirilchuk Svetlana; Nalivaychenko Ekaterina (π-Economy)
The objective of the study: to reveal the relationship between industrial digitalization and dynamic changes in the labor economy in the context of the introduction of Industry 4.0 and 5.0 technologies in the Republic of Crimea, as well as to identify the impact of these changes on production processes, employment and qualifications of the workforce. Research methodology: logical, systemic and functional-differential approaches, as well as statistical analysis and synthesis. These methods allow for a deeper understanding of the impact of digitalization on the industrial sector and its relationship to the world of work. Research results: the first part of the study examines the effectiveness of digitalization of the industrial sector of the Crimean region in the context of Industry 4.0, the second part of the study provides a description of dynamic changes in the labor economy of the Crimean region in the context of Industry 5.0. The focus is on the impact of digitalization on production processes, employment and qualifications of the workforce in the context of the transition to the sixth and seventh technological paradigms. The results of the analysis show that, despite the positive trends in increasing the importance of the contribution of human capital to economic growth, the development of high-performance jobs and the implementation of digital technologies, there are significant challenges, such as declining labor productivity and lagging behind the pace of nominal wage growth. In general, the dynamics of industrial development performance indicators in the Crimean region is lower than the Russian average. Recommendations: The existing problems can be overcome by activating the possibilities of industrial digitalization, which requires increased investment in fixed assets, ensuring access to modern technologies and production tools, effective use of digital resources, and the development of a digital culture of employees. The originality of the research and the author's contribution: the imbalances in the industries of the Crimean region were identified and recommendations were formulated to improve the efficiency of the industry through the development of infrastructure for digital transformation and key technologies.